Case 1: Suppose we have two terms 7ab and 3ab. When we multiply these two terms, we get 7ab x 3ab = (7 x 3) a^{1 + 1} . b^{1 + 1 }( Therefore, x^{m} . x^{n} = x^{m + n}) = 21a^{2}b^{2}. The product of 7ab x 3ab will be the same as that of 3ab x 7ab. Irrespective of the order of multiplication, the product of two positive terms will be a positive term. Similarly, the product of 8a^{2}b and 3a^{2}b = (8 x 3) a^{2} . a^{2 }b . b = 24 a^{2+2} b^{1+1} = 24 a^{4} b^{2 } Case 2: Suppose we have to compute the product of -7ab and -3ab, it will be equal to (-7 x -3) a^{2}b^{2} = 21a^{2}b^{2}, i.e. multiplication of two negative quantities gives us a positive quantity.
Case 1: Suppose we have two terms 7ab and 3ab. When we multiply these two terms, we get 7ab x 3ab = (7 x 3) a^{1 + 1} . b^{1 + 1 }( Therefore, x^{m} . x^{n} = x^{m + n}) = 21a^{2}b^{2}. The product of 7ab x 3ab will be the same as that of 3ab x 7ab. Irrespective of the order of multiplication, the product of two positive terms will be a positive term.
Similarly, the product of 8a^{2}b and 3a^{2}b
= (8 x 3) a^{2} . a^{2 }b . b
= 24 a^{2+2} b^{1+1}
= 24 a^{4} b^{2 }
Case 2: Suppose we have to compute the product of -7ab and -3ab, it will be equal to (-7 x -3) a^{2}b^{2} = 21a^{2}b^{2}, i.e. multiplication of two negative quantities gives us a positive quantity.